Physical activity and mental health: Exploring the role of movement and posture in reducing stress and enhancing well-being - Li, Tiantian; Liu, Fang; Zhang, Lei; Ma, Chao (Molecular & Cellular Biomechanics, 2024)
In recent years, mental health issues such as stress, anxiety, and depression have become increasingly prevalent worldwide, necessitating the exploration of practical and accessible interventions. This paper investigates the role of physical activity and posture in reducing stress and enhancing mental well-being, focusing on everyday movements and body alignment. Drawing on existing research, we explore the neurochemical and psychological mechanisms by which physical activity influences mental health, emphasizing the impact of both moderate and high-intensity exercises. The role of proper posture in managing stress and promoting relaxation is examined, focusing on postural interventions such as ergonomic adjustments and mindfulness practices. A case study conducted in Shanghai, China, assesses the effectiveness of a workplace-based intervention involving physical activity and posture correction among employees with high stress levels. In the 12-week intervention, participants in the intervention group experienced a 25% reduction in perceived stress, a 30% decrease in anxiety, and a 20% reduction in depressive symptoms. Physiological markers also improved, with a 15% increase in heart rate variability (HRV) and an 18% reduction in cortisol levels. In contrast, the control group showed no significant changes. These findings underscore the value of integrating regular physical activity and posture correction into daily routines to enhance psychological and physiological well-being. The study concludes with practical recommendations for incorporating these interventions into workplace and personal environments to promote long-term mental health.